Preparation of an intelligent pH film based on biodegradable polymers and roselle anthocyanins for monitoring pork freshness. (30th January 2019) - Zhang, Junjun; Zou, Xiaobo; Zhai, Xiaodong; Huang, XiaoWei; Jiang, Caiping; Holmes, Mel
Highlights: Three different films were prepared by using two substances of starch, polyvinyl alcohol and chitosan. The starch/polyvinyl alcohol/roselle anthocyanins film had the highest antioxidant activity and the best color stability. The starch/polyvinyl alcohol/roselle anthocyanins film was used for pork freshness. Abstract: This study aims to develop an intelligent indicating film based on biodegradable polymers incorporated with roselle anthocyanins to monitor pork freshness. Three different films were prepared by using two substances of starch, polyvinyl alcohol and chitosan. The UV–vis spectra and color of anthocyanins changed at pH 2–12. SEM photographs showed that the compatibility of films was improved with the addition of anthocyanins. Furthermore, the polyvinyl alcohol/chitosan/roselle anthocyanins film had the highest tensile strength (98.28 MPa). The starch/polyvinyl alcohol/roselle anthocyanins film had the highest antioxidant activity (524.07%) and the best color stability. The starch/polyvinyl alcohol/roselle anthocyanins film showed visible changes from red to green when employed to monitor the freshness of pork stored at 25 °C, before the TVB-N value of the pork gradually increased to the rejection limit (15 mg/100 g) at 36 h. Therefore, the indicator film can be used to monitor pork freshness for intelligent packaging.